Malawi : Mobilizing Long-Term Finance for Infrastructure - World Bank (World Bank, Washington, DC, 2021)
Malawi has a large infrastructure gap, which is beyond what the government can afford. Over the period of two decades (1998-2017), the total public investment in Malawi averaged 4.18 percent of GDP per year while in the energy and water and sanitation sectors alone, a similar level of investment, about 4 percent of GDP annually, will be required to meet the growing infrastructure demand. At the same time, the fiscal space has been decreasing as evidenced by the growing public debt, total public debt increased from 28 percent of GDP in 2007 to 63 percent of GDP in 2019. In this context, Malawi needs to make well though-out choices in prioritizing its investment program, improve the efficiency of infrastructure planning and implementation, and crowd-in financing from both foreign and domestic private investors. The report argues that the preconditions for enabling the needed transformation exist. Improvements in the macro-economic environment in the past five years makes private investment more possible, although in the short-term, the COVID-19 pandemic will have a negative impact as risk aversion increases. The regulatory framework for public-private partnerships (PPPs) is in place and further evolving, and a large PPP in the energy sector (about $1 billion) is currently under development. Domestic long-term investors (pension funds and life insurance companies) have been rapidly accumulating long-term funds in the past few years (especially after regulatory reforms to introduce a mandatory pension system) and are looking for long-term investment opportunities. The report proposes that the Government of Malawi (GoM) undertakes reforms to improve the fiscal space and in turn increase infrastructure investments through its own resources and encourage the role of the private sector in the financing of infrastructure. More specifically, the GoM can (a) improve the efficiency of the public investment management framework and integrate it with the PPP framework, (b) improve the efficiency of infrastructure delivering state-owned enterprises, (c) advance the PPP program by allocating resources to develop the needed capacity, and (d) deepen the domestic long-term finance market by availing long-term liquidity facilities to catalyze bank lending to infrastructure, issuing regulations to expand the range of long-term finance instruments and vehicles, and introducing a program of transaction testing, piloting, and market sounding to systematically link supply and demand side of the infrastructure finance, among others.